Raman spectroscopy mapping of changes in the organization and relative quantities of cell wall polymers in bast fiber cell walls of flax plants exposed to gravitropic stress - Blervacq, Anne-Sophie; Moreau, Myriam; Duputié, Anne; De Waele, Isabelle; Duponchel, Ludovic; Hawkins, Simon (Frontiers in Plant Science, 2022)
Flax is an important fiber crop that is subject to lodging. In order to gain more information about the potential role of the bast fiber cell wall in the return to the vertical position, 6-week-old flax plants were subjected to a long-term (6 week) gravitropic stress by stem tilting in an experimental set-up that excluded autotropism. Changes in the relative amounts and distribution of cell wall polymers in flax bast fibers were determined by Raman vibrational spectroscopy. Following spectra acquisition, datasets (control, pulling- and opposite sides) were analyzed by principal component analysis, PC score imaging, and Raman chemical cartography of significant chemical bonds. Our results show that gravitropic stress induces significant changes in the composition and distribution of cell wall polymers in both pulling side and opposite side fibers. Significant increases in the amounts of cellulose, xyloglucans and xylans were observed within the thick S2/G layer of stressed fibers compared to control fibers. These increases occurred throughout the S2/G layer of opposite fibers, but were restricted to discrete micro-domains within the S2/G layer of pulling-side fibers. Gravitropic stress also led to smaller, but still significant increases in lignin, pectin and glucomannans. The use of a Raman imaging approach demonstrated that the observed stress-induced changes in cell wall polymer distribution and relative quantities differed not only between pulling and opposite side fibers, but also between different cell wall layers considered